N and C-atoms in R (Ar)-N\(_2\)-CH\(_4\) Flowing Afterglows at High Pressure - Ricard, André (Plasmas Afterglows with N2 for Surface Treatments synthesis 2024, 2025)
The plasma and afterglows of N2 and Ar-N2 HF discharges are presently studied to precise the N-atom production in afterglow conditions at high gas pressure (up to the atmospheric gas pressure). The production of N-atom density has been analyzed in Ar-N2 high-pressure flowing afterglows after HF plasmas at a frequency from 13.6 Mhz to 2450 MHz. The plasma length increased when the HF frequency decreased from 2450 to 13.6 MHz and by lowering x in the Ar-xN2 gas mixture. It was found that the N+N recombination on the N2(B,v’) states was reduced by 2.5 for v’=11, by 10 for v’=8 and by 30 for v’=0 by going from pure N2 to Ar-2%N2. The production of N and C-atoms in a double Ar-N2 and Ar-CH4 HF flowing afterglows was in the ranges of 1015cm-3 and 1012cm-3, respectively. In Ar-N2-xCH4 with x=10-3 – 10-2 there was a drop of N and C-atoms at x=10-2 which should result in N+CH3 reactions. The CH3 density was about 4 1011 cm-3 in an Ar-17%N2-1%CH4 gas mixture at 14 Torr.